Study on the Hydrodynamics of a Cownose Ray’s Flapping Pectoral Fin Model near the Ground - Yang Luo; Zhexing Hou; Dongyang Chen; Tongshi Xu; Qiaogao Huang; Pengcheng Ye; Guang Pan (Journal of Marine Science and Engineering)
Cownose rays typically swim close to the ocean floor, and the nearby substrate inevitably influences their swimming performance. In this research, we numerically investigate the propulsive capability of cownose rays swimming near the ground by resolving three-dimensional viscous unsteady Navier–Stokes equations. The ground effect generally has a favorable impact on swimming. The thrust and lift increase as the near-substrate distance decreases. Nevertheless, a body length is the recommended distance from the ground, at which the flapping efficiency and swimming stability obtain a good trade-off. The increase in lift is due to the pressure difference between the dorsal and ventral surfaces of the ray, and the thrust boost is due to the enhanced shear vortex at the fin’s leading edge when swimming near the substrate. Our results indicate that the ground effect is more noticeable when the fin flaps are symmetrical compared to asymmetrical. In asymmetric flapping, the hydrodynamic performance improves at a smaller value than the half-amplitude ratio (HAR). The frequency of flapping also significantly affects swimming performance. We find that a superior flapping frequency, at which maximum efficiency is reached, occurs when flapping close to the substrate, and this superior frequency is consistent with the behavior of our model’s biological counterpart.